Letter (copy) : Position of Spanish seamen - Tewson, Vincent
025a-0139-001 Secretary's. HVT/FC/370. 9th March, 1939. Mr. E.N. Cooper, The Home Office Aliens' Department, Cleland House, Page Street, S.W.1. Dear Mr. Cooper, POSITION OF SPANISH SEAMEN. With reference to Mr. Luckhurst Scott's telephone conversation with you on Tuesday last I am now enclosing a list forwarded to me by the Mid-Atlantic Shipping Company giving the names of the ships concerned, the Ports where they are lying, the names of the Captains and the number of crew. I understood from Mr. Scott that you would send us a copy of the list which is in your hands in order that we might check the particulars given in both lists. Perhaps, therefore, you would kindly let me have a copy of the list in your possession. Yours faithfully, Assistant Secretary. List. 292/946/25a/139